Effects of Wood Modification Using Natural Resin on Wood Quality and Bonding Properties - Muhammad Navis Rofii; Ragil Widyorini; Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2019)
The aim of this study was to investigate the effect of gum rosin impregnation upon a low quality young teak wood in order to enhance its quality. The main objective of the treatment was to enhance the dimensional stability, as well as strength and to reduce the hygroscopicity. A 15-years old thinned teak wood (Tectona grandis L.f.) and gum rosin from Pinus merkusii Jungh. et de Vries were used for wood modification treatment by impregnation. Three kinds of non-polar solvents, i.e. turpentine oil, petroleum oil and n-hexane-, were used to make gum rosin solution. The results indicated that gum rosin impregnation did not markedly enhance the quality of young teak wood in terms of either dimensional stability or hygroscopicity; however, a little enhancement was delivered by using 15% gum rosin solution with n-hexane as the solvent. The treatment with petroleum oil solvent (at concentration of 7.5%) and at 15% concentration with n-hexane solvent resulted in highest bending properties. The highest bonding strength in dry condition was resulted by treatment with turpentine oil solvent.